ANALISIS KEMAMPUAN MATEMATIKA TERHADAP HASIL BELAJAR SISWA SMA PADA MATERI LARUTAN PENYANGGA (JS (JURNAL SEKOLAH), 2025)
Abstract: The purpose of this study was to determine the relationship between math skills and chemistry learning outcomes of MAN 1 Medan students. This research is quantitative using basic linear regression analysis. The sample was taken by purposive sampling and a sample of one class was selected, namely XI MIPA 2. The instrument used was a test consisting of 10 essay questions on each chemistry question sheet of buffer solution and math ability. Analysis of research instruments was carried out with qualitative analysis and hypothesis testing was carried out with correlation and determination coefficient tests. The results of data analysis showed a positive and strong relationship between math ability and chemistry learning outcomes, this is evidenced by the acquisition of a sig value of 0.00